1995
DOI: 10.1111/j.1365-3148.1995.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum alanine aminotransferase (ALT) to body mass index (BMI) in blood donors: the need to correct ALT for BMI in blood donor screening

Abstract: A study was carried out on 1,028 voluntary blood donors to see how body mass index (BMI) correlated with the serum alanine amino transferase (ALT) activity. The mean ALT (U/l) values were 19.35, 27.63, 40.79 and 54.41 in the four BMI categories of < or = 20, 20.1-25, 25.1-30 and > 30, respectively. This study showed that the mean serum ALT level of obese subjects (BMI > 30 kg/m2), compared with the two categories of normal subjects (i.e. BMI < or = 20 and BMI = 20.1-25 kg/m2), was increased by 2.8 and 1.96 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It is widely acknowledged that obesity is one of the most important factors responsible for elevated BP in children and adolescents ( 46 , 47 ). In accordance with a population-based study in Nigeria, where BMI and WC were revealed as risk factors for hypertension and prehypertension, we found that both general obesity and central obesity were associated factors of childhood hypertension ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that obesity is one of the most important factors responsible for elevated BP in children and adolescents ( 46 , 47 ). In accordance with a population-based study in Nigeria, where BMI and WC were revealed as risk factors for hypertension and prehypertension, we found that both general obesity and central obesity were associated factors of childhood hypertension ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for the lack of efficacy is that, in addition to infectious agents with liver tropism, there are other factors that may result in an increase of ALT levels, such as obesity [10–12], alcohol intake [13] and drugs. Moreover, there are extrahepatic sources of ALT, such as the muscle [14], kidney and red blood cells [15], which can result in an increase of the ALT levels in serum.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a great number of donors are deferred because of elevated ALT levels (Kim et al, 2008). However, the efficiency of ALT testing to reduce hepatitis transmission is controversial because there are many other causes of elevated serum ALT levels (Bizzaro et al, 1992;Ramesh et al, 1995). Serological testing for the detection of antibodies to certain viruses is used to confirm infection.…”
Section: Introductionmentioning
confidence: 99%